PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Anggela, Nicole; Rasyid, Rosmita (Jurnal Paradigma Akuntansi, 2025)
This study examines the effect of liquidity, solvency and profitability on share prices of energy sector companies on the Indonesia Stock Exchange for the period 2020–2022. In this study, liquidity is measured using the Quick Ratio (QR), solvency is measured using the Debt to Assets Ratio (DAR), and profitability is measured using the Profitability Ratio return on assets (ROA). Purposive sampling is a technique used for sample preparation. There are 35 energy-related businesses listed on the IDX for the 2020–2022 period and meet the criteria. The analytical method used is multiple linear regression analysis. The tool used to process the data collected is IBM SPSS Statistics 25. The results of the study show that there is a simultaneous effect of liquidity ratios (QR), solvency (DAR), and profitability (ROA) on stock prices in energy sector companies listed on the IDX for the period 2020-2022. Meanwhile, partially it shows that liquidity (QR) and profitability (ROA) have a positive and significant effect on stock prices in energy sector companies listed on the IDX for the 2020-2022 period, while partially there is no solvency effect on stock prices in energy sector companies that listed on the IDX for the 2020-2022 period.